The importance of a historical perspective in language shift studies: focus on minority groups in Kuching - David, M.K. (2009)
When a minority community begins losing its mother tongue to a more dominant one, this can be viewed as that heritage language being potentially on the path to extinction. An earlier study to investigate reasons for language shift in Sabah and Sarawak clearly shows both macro and micro variables are significant in causing language shift (David and Dealwis, 2008). In fact way back in 1952 Weinrich cited a range of ten variables as decisive factors in determining language shift. These are geography, indigenousness, cultural or group membership, religion, sex age, social status, occupation, rural versus urban residence and race. More recently Edwards (1992) argues that "sociolinguistic forays into minority language matters-and many others too-must be interdisciplinary". Language shift therefore needs to be considered also from a historical perspective. This is by itself a pertinent aspect that needs to be addressed when conducting research among minority groups. We need to understand the history of the minority communities in order to explain the reasons for language shift. History includes when they came, where they came from, socio-economic and political situations in the country of domicile etc. In this study, the Tamil, Malayalee, Telegu and Indian Muslims communities in Kuching, Sarawak are examined in order to show how historical variables can influence language choice. The paper concludes that researchers conducting studies on language maintenance and shift among minority groups who ignore these historical variables are doing so at their own risk.